Government-guaranteed credit and populism - Ernest Dautovic; Robin Hsieh (European Central Bank (ECB), 2024)
The phenomenon of political populism and its financial determinants have proved elusive. We utilise the sudden and uneven change in credit conditions during the COVID-19 pandemic and the unprecedented government credit guarantee programme in France to investigate whether liquidity support to firms affects political preferences. Drawing on credit registry data - which provides the universe of loans and credit lines to firms - we build a postcode-municipality-level dataset and show that government-guaranteed credit reduced the support for the far right but increased it for the incumbent. The underlying economic channel shows that credit guarantees preserved employment, which in turn influenced political preferences. Effects are driven by microenterprises, predominantly self-employed businesses in which the employee-owner-voter is fully aware of the government financial support, i.e., where government support is more salient. This study does not aim to evaluate policies to address the popularity of populist politics.
Keywords: D72; E44; G18; G21; H81; 330; Firms; Credit; Government guarantees; Fiscal policy; Populism